2022
DOI: 10.1002/srin.202200246
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Study of Hot Deformation Behavior and Microstructure Evolution of Rack Steels with and without Segregation

Abstract: In order to compare the hot deformation behavior and microstructure evolution of the rack steels with and without segregation, hot compression tests are carried out in the temperature range of 1173–1423 K and the strain rate range of 0.01–10 s−1 on a DIL805A/D quenching and deformation dilatometer. The flow stress, constitutive relation, processing map, and microstructure characterization are investigated. The results show that the flow stress increases with the increase of strain rate and the decrease of defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Thus, The KAM maps can intuitively suggest the deformation energy. [37] Figure 9a-c showed the KAM value under different deformation conditions. The high KAM value at a temperature of 880 °C and a strain rate of 0.1 s À1 indicated that severe plastic deformation occurred within the crystal, leading to large lattice distortions and complex dislocation motions.…”
Section: Microstructure Observation Of Stable Regionsmentioning
confidence: 99%
“…Thus, The KAM maps can intuitively suggest the deformation energy. [37] Figure 9a-c showed the KAM value under different deformation conditions. The high KAM value at a temperature of 880 °C and a strain rate of 0.1 s À1 indicated that severe plastic deformation occurred within the crystal, leading to large lattice distortions and complex dislocation motions.…”
Section: Microstructure Observation Of Stable Regionsmentioning
confidence: 99%
“…The Arrhenius model [10] and the Johnson-Cook (J-C) model [11] are two widely used phenomenological models, which have been successfully used to predict the flow behavior of a variety of materials. [12][13][14] However, these models are of little metallurgical significance and cannot reflect the evolution of microstructure. Therefore, different types of physical constitutive models have been proposed, including Zerilli-Armstrong (Z-A) model, [15] model based on dynamic recovery (DRV) and DRX mechanisms, [16,17] model based on dislocation mechanism, [18] and so on; these physical models are proposed with consideration of micromechanisms but have a large number of material constants.…”
Section: Introductionmentioning
confidence: 99%